Terminology of Welfare State in the Quran On the Dimensions of Constitutional Law - Rohmah, Siti Ngainnur; Yunus, Nur Rohim (ADALAH, 2024)
This essay discusses the terminology of "welfare state" in the Quran from the constitutional law perspective. As the primary source of Islamic teachings, the Quran offers a deep and comprehensive concept of a welfare state that includes social justice, environmental sustainability, and a balance between individual rights and social obligations. This research explores three main aspects: fair law enforcement, infrastructure development that supports welfare, and community empowerment. In the Quran, the government has a significant responsibility to ensure the welfare of all society through transparency, justice and accountability in the management of state affairs. This essay concludes that the Quran provides moral and spiritual guidance and a comprehensive framework for creating a just and sustainable welfare state. Implementing these principles in constitutional law can form the basis for a government capable of bringing prosperity to all the people.